PENGARUH GAYA KEPEMIMPINAN, MOTIVASI KERJA, DAN KINERJA KARYAWAN TERHADAP KUALITAS PRODUK KABEL BODY MOBIL PADA PT. KARANGANYAR INDO AUTO SYSTEMS - Sulistya, Sulistya; Rohwiyati, Rohwiyati (Surakarta Management Journal, 2023)
This study aims to determine the influence of leadership style, work motivation and employee performance on the quality of car body cable products at PT. Karanganyar Indo Auto Systems both partially and simultaneously. This research uses quantitative methods and data collection techniques through observation, interviews and the distribution of questionnaires. The population in this study were employees of PT. Karanganyar Indo Auto Systems quallity assurance department/section. The sampling technique used was simple random sampling with a total of 58 respondents, where the sample size was determined through thearikunto formula. Data analysis using multiple linear regression analysis with IBM SPSS Statistical 22 test tool. The results showed that partially leadership style has a significant positive effect on product quality, partial work motivation has a significant positive effect on product quality, partially employee performance has a significant positive effect on product quality, simultaneously leadership style, work motivation and employee performance have a significant positive effect on product quality